Pemberdayaan Petani Lokal Suku Tehit melalui Edukasi Teknik Penyemaian Benih Tanaman yang Efisien - Zulkarnain Sangadji; Ihsan Febriadi; Riskawati Riskawati; Ishak Musaad; Bertha Mangallo; Amilda Auri; Kesya Kesya; Mersedes Fati (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program aims to improve the capacity of local Tehit farmers in Southwest Papua to implement efficient and environmentally friendly seeding techniques. The program was implemented through a participatory approach, including outreach, training, and direct field mentoring. The results showed active community participation in all stages, as well as a 65% increase in knowledge, from 25% before training to 90% after mentoring. This improvement directly impacted seed germination success, which increased from an average of 60–65% to 88–92%. Furthermore, the community began using nursery containers with pot trays, contributing to reduced plastic waste and increased environmental awareness. Overall, the program successfully strengthened farmer capacity, increased crop productivity, and supported sustainable agricultural practices. This program directly contributes to the achievement of the Sustainable Development Goals (SDGs), particularly SDG 1 (No Poverty), SDG 2 (Zero Hunger), SDG 12 (Responsible Consumption and Production), and SDG 15 (Life on Land).